Desenvolvimento de framework para gerenciamento de ferramentas em fornecedores terceiros: uma pesquisa-ação em uma empresa de linha branca - Favatto Filho, Antonio Silvio (Universidade Federal de São Carlos, 2024)
In the context of household appliances studied in this research, the application of preventive maintenance principles in the supply chain is a major challenge due to the difficulty of communication, integration and cooperation between customers and suppliers. This is even more relevant when suppliers not only deliver parts and components, but also have tools from customer companies on loan, where responsibilities for tool maintenance are shared. This study therefore proposes a framework for incorporating preventive maintenance concepts into the maintenance of tools that are outsourced to third-party suppliers. The concepts presented in the framework were incorporated into software that includes a control dashboard to support the management of tool maintenance at third-party suppliers. To achieve this objective, the action research method was applied, consisting of three cycles. The first cycle was a development stage for the framework and software premises, the second cycle consisted of implementing the process and software guidelines at a first supplier in the home appliance chain, and the third cycle was responsible for expanding the process to a second supplier. As a result of the study, a structured framework is presented which is the basis for the software and dashboard that support the management of the proposed new model for preventive maintenance. The framework indicates a path for implementing and managing preventive maintenance at suppliers based on theory. In addition, the action research showed that the proposed framework is capable of generating greater integration and cooperation between the client company and its suppliers, increasing the companies' performance levels in the supply chain. The implementation of the framework through software and a dashboard enabled the implementation of preventive maintenance, which resulted in better quality levels in the suppliers' parts and fewer line stoppages. The limitations of the work are related to the impossibility of generalizing the results found through action research and also to the lack of quantitative analysis of the results obtained.
Framework proposal for preventive maintenance in third-party suppliers: an action research in the white goods industry
Keywords: Framework; Supplier quality management; Total productive maintenance; Supply chain integration; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO